Precipitações intensas e seus impactos no ambiente urbano de Uberlândia – MG - Silva, Nathalie Ribeiro (2018)
The cities are considered as the most significant modifications that man makes on the geographical space. As long as cities grow, their vulnerability to climate increases. It is not uncommon in Brazil for the occurrence of disasters in large urban centers related to atmospheric phenomena. The urbanization process has been responsible for the immense impermeable areas where the concentrated rains do not find spaces for the infiltration contributing to the aggravation of the surface runoff. The city of Uberlândia-MG is inserted in this context. The existence of a large waterproofed area, asphalted and occupied by buildings, together with the channeling of the streams, deficiency in the drainage system and the removal of the vegetation cover, decreases year by year the infiltration área. It is in this sense that the objective of this work sought to identify the intense pluviometric events that impacted the urban area of Uberlândia-MG. For that, the records of the Municipal Civil Defense service, due to rain, were used between the years 2011 to 2016, together with the pluviometric data of the city's Meteorological Station, relating them to the repercussion of these episodes in the newspapers.The research was carried out based on the theory of the Urban Climate System (S.C.U.) proposed by Monteiro (1976) using the channel of human perception, impact of rain. Data analysis showed that, mainly summer rains, from October to March, with precipitations between 20 and 30 mm were sufficient to trigger the impacts such as flooding, flooding and asphalt detachment. All the urban area of Uberlândia was susceptible to rainfall impacts during the analyzed period, a fact that shows how the effects of urbanization affect all sectors of the city when intense rainfall occurs.